PENGARUH PEMBERIAN ASI TERHADAP INFEKSI SALURAN KEMIH PADA ANAK - , Budhi Pranowo, Prof. dr. Sunartini H., Ph.D, Sp AK ([Yogyakarta] : Universitas Gadjah Mada, 2012)
UTI Incidence and prevalence of Urinary Tract Infection (UTI) is vary in children. may lead to complication, both in short term (bacteremia and meningitis) and in long term (hypertension, decreasing of renal function, or permanent renal impairment). Breastfeeding has been proved to reduce the incidence of acute infections such as diarrhea, otitis media, and respiratory tract infections. The aim of this study is todetermine the effect of breastfeeding on the incidence of urinary tract infections in children. Case control study was obtained in outpatient children agedâ¤2 years with fever (â¥ 380C) from January 2011to July2011. UTI group (leucocyte esterase and nitrit positive) was compared to Non UTI group ((leucocyte esterase and nitrit negative) by 1:3 ratio. Breastfeeding status was measured in both group using questionnaire. There are significant differences between children who is still breastfed compared to children who is not breastfed on the incidence ofUTIin children â¤2 years(OR 5,5